Eksistensi Badan Usaha Milik Nagari (BUMNAG) Dalam Meningkatkan Pendapatan Nagari di Nagari Tabek Patah Kecamatan Salimpaung Kabupaten Tanah Datar - Fitri Yul Dewi Marta (PT FORMOSA CENDEKIA GLOBAL, 2022)
West Sumatra as a province in the State of Indonesia uses the term Nagari system for the lowest administrative area where the BUMdes program in West Sumatra is also referred to as Badan Usaha Milik Nagari (BUMNag). The purpose of this study is to analyze the existence of Badan Usaha Milik Nagari (BUMNag) in increasing Nagari income in Nagari Tabek Patah, Salimpaung District, Tanah Datar Regency, to find out the obstacles faced and provide efforts in developing Nagari-Owned Enterprises (BUMNag) in increasing Nagari income. in Nagari Tabek Patah, Salimpaung District, Tanah Datar Regency. This study uses a descriptive analysis method with a qualitative approach. The results of the discussion of this study that the existence of Badan Usaha Milik Nagari (BUMNag) in increasing Nagari income in Nagari Tabek Patah, Salimpaung District, Tanah Datar Regency, West Sumatra Province can be said to be still not visible due to several obstacles from various factors. The recommended efforts in this paper include, among others, the need to conduct a briefing for BUMNag management who will manage BUMNag on a regular basis so that BUMNag management can run well. Choosing good Human Resources (HR) for the advancement of BUMNag in the Tabek Patah Nagari Government so that they can contribute to increasing Nagari's Original Income. It is necessary to speed up the process of forming new BUMNag to replace the previous BUMNag that had suffered losses so that the existence of the Tabek Patah BUMNag could look good and develop in order to increase Nagari's original income.